2021
DOI: 10.1007/s00158-021-03030-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel p-harmonic descent approach applied to fluid dynamic shape optimization

Abstract: We introduce a novel method for the implementation of shape optimization for non-parameterized shapes in fluid dynamics applications, where we propose to use the shape derivative to determine deformation fields with the help of the $$p-$$ p - Laplacian for $$p > 2$$ p > 2 . This approach is closely related to the computa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
(54 reference statements)
0
34
0
Order By: Relevance
“…( 55) leads to a linear system, which is solvable by use of standard techniques such the CG-method. It is reported in [13], that the p-Laplacian metric has particular advantages in resolution of sharp edges or kinks of optimal shapes. Illustration of this is not the goal of this paper.…”
Section: Numerical Results and Comparison Of Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 55) leads to a linear system, which is solvable by use of standard techniques such the CG-method. It is reported in [13], that the p-Laplacian metric has particular advantages in resolution of sharp edges or kinks of optimal shapes. Illustration of this is not the goal of this paper.…”
Section: Numerical Results and Comparison Of Algorithmsmentioning
confidence: 99%
“…To be more specific, we test two bilinear forms and four regularizations of gradients for a standard gradient descent algorithm with a backtracking line search. The two bilinear forms are given by the linear elasticity as found in [17] and the p-Laplacian inspired by [13] and studies found in [4]. Different gradients tested will be the unregularized, the shape regularized, the shape and volume regularized, and the shape and volume regularized one with varying outer boundary.…”
Section: Implementation Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An more recent paper by Müller, Kühl, et.al. [7] suggests solving a p-Laplace problem as a relaxation for the steepest descent step. This is done in a free node optimization setting and can deal effectively with situations where the optimum might contain points or edges in the shape.…”
Section: Sobolev Smoothing On Function Spacesmentioning
confidence: 99%
“…Hence, using a coarser parameterization, which only produces shapes of sufficient regularity, circumvents this problem [5]. The most popular solution to solve this problem is to apply an elliptic partial differential equation to smooth the gradient [6,7]. This is equivalent to a reinterpretation of the gradient in a search space of higher regularity.…”
Section: Introductionmentioning
confidence: 99%